The Effect of Leg Length, VO2 Max and Core Stability on 50 m Freestyle Swimming Speed - Fidi Azka, Muhamad; Pelana, Ramdan; Wasan, Aan; Unju Subandi, Oman (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
Swimming is a sport that makes speed as one of the benchmarks of assessment, especially short distance swimming. speed in swimming is the maximum speed that is cyclical or speed whose movements are repeated, the same form of speed as speed in running (sprint). This study aims to explore the effect of leg length, VO2 Max and core stability on 50m freestyle swimming speed. This study uses quantitative methods with a correlation research design (causality study). This study involved 30 people as samples who had been selected through purposive sampling technique. The results showed that (1) there is a direct effect of leg length on 50 m freestyle swimming speed (2) there is a direct effect of VO2 Max on 50 m freestyle swimming speed (3) there is a direct effect of Core Stability on 50 m freestyle swimming speed (4) there is a direct effect of Leg Length on Core Stability (5) there is a direct effect of VO2 Max on Core Stability (6) indirectly leg length has a significant effect on 50 m freestyle swimming speed through core stability (7) indirectly VO2 Max has a significant effect on 50 m freestyle swimming speed through core stability. Based on these seven findings, it can be concluded that the variables of leg length, VO2 Max and core stability have a mutual influence on 50m freestyle swimming speed.